2022
DOI: 10.3390/cells11142241
|View full text |Cite
|
Sign up to set email alerts
|

Muramyl Dipeptide Administration Delays Alzheimer’s Disease Physiopathology via NOD2 Receptors

Abstract: Alzheimer’s disease (AD) is the most common form of dementia in the world. The prevalence is steadily increasing due to an aging population and the lack of effective treatments. However, modulation of innate immune cells is a new therapeutic avenue, which is quite effective at delaying disease onset and improving cognitive decline. Methods: We studied the effect of the NOD2 receptor ligand muramyl dipeptide (MDP) on the modulation of the innate immune cells, namely patrolling monocytes and microglia. We admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…By contrast, we have glimpses that molecular adjuvants might be of significant benefit in AD. MDP administration in AD model mice is reported to delay AD-related pathology [ 64 ]. Another adjuvant molecule, the CpG oligodeoxynucleotide 2006 (CpG ODN), has shown promise in mouse AD models [ 65 ] and produced favorable reductions in naturally occurring amyloid pathology in elderly squirrel monkeys [ 66 ]; clinical trials are planned in New York (NCT05606341).…”
Section: Adjuvants and Alzheimer’s Disease: Could Bcg Be Replaced By ...mentioning
confidence: 99%
“…By contrast, we have glimpses that molecular adjuvants might be of significant benefit in AD. MDP administration in AD model mice is reported to delay AD-related pathology [ 64 ]. Another adjuvant molecule, the CpG oligodeoxynucleotide 2006 (CpG ODN), has shown promise in mouse AD models [ 65 ] and produced favorable reductions in naturally occurring amyloid pathology in elderly squirrel monkeys [ 66 ]; clinical trials are planned in New York (NCT05606341).…”
Section: Adjuvants and Alzheimer’s Disease: Could Bcg Be Replaced By ...mentioning
confidence: 99%
“…They demonstrated that patrolling monocytes were the primary phagocytic cells responsible for clearing Aβ from the brain, suggesting that these cells may play an important role in the pathogenesis of AD [ 12 ]. These studies were recently reviewed by us [ 6 ]. Taken together, these studies suggest that patrolling monocytes have a unique ability to phagocytose cellular debris and foreign material in a variety of tissues, including the brain vascular system.…”
Section: Nod2 In Alzheimer’s Diseasesmentioning
confidence: 99%
“…The recruitment of patrolling monocytes to vascular amyloid deposits is still not fully understood, but it is believed that CCR2, CCR5, and CX3CR1 each are partially involved in their recruitment [ 14 , 15 ]. Additionally, the intravital two-photon microscopy of our laboratory has demonstrated that patrolling monocytes are specifically attracted to the luminal wall of Aβ-positive vasculatures, and their removal has been shown to lead to a significant decrease in Aβ plaques [ 6 ]. This suggests that increasing the number of patrolling monocytes in the vasculature could be a potential therapeutic avenue for AD.…”
Section: Nod2 In Alzheimer’s Diseasesmentioning
confidence: 99%
See 2 more Smart Citations